2021
DOI: 10.3991/ijet.v16i02.13639
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding the Students’ Acceptance of MOOCs: A Unified Theory of Acceptance and Use of Technology (UTAUT)

Abstract: Massive Open student’s courses (MOOC) have stimulated the efforts made for improving the learning techniques and enhancing it the spectrum for students learning. Unfortunately, the acceptance of MOOC as a learning instrument re-mained low, which is perceived as an entertainment tool rather than an academic tool, particularly in developing countries. The study evaluated the student’s adap-tation of MOOC as an academic tool. It developed an understanding of the asso-ciated factors which impact the students’ deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
6
18
1
Order By: Relevance
“…Previous studies have found that, with the improvement of PE, SI, EE, and facilitating conditions (Awwad and Al-Majali, 2015;Altalhi, 2021;Alvi, 2021), the willingness of college students to accept AI-assisted learning environments increased significantly; the same result was found in this study.…”
Section: Pe Si and Ee Had A Positive Significant Relationship With Co...supporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have found that, with the improvement of PE, SI, EE, and facilitating conditions (Awwad and Al-Majali, 2015;Altalhi, 2021;Alvi, 2021), the willingness of college students to accept AI-assisted learning environments increased significantly; the same result was found in this study.…”
Section: Pe Si and Ee Had A Positive Significant Relationship With Co...supporting
confidence: 87%
“…According to existing studies, EE plays an indispensable role in the application of technology (Liebenberg et al, 2018). Altalhi (2021) conducted a survey of 150 students on MOOC acceptance and adaptability, and the data showed that effort expectations had a significant impact on student acceptance of MOOCs. When Yang et al (2019) studied how the integrated model of UTAUT and Connected Classroom Climate (CCC) affected students' acceptance of cloud classrooms, they found that effort expectations had a significant effect.…”
Section: Effort Expectancymentioning
confidence: 99%
“…In addition, Alalwan et al (2017) studied the factors affecting mobile banking adoption by the customers of Jordanian bank using modified model, which has assimilated constructs from the UTAUT2 along with TR. Further, the study of Altalhi (2021) aimed to evaluate empirically factors influencing the student's BI to use massive open online course as an elearning instrument through the addition of different factors such as self-efficacy and attitude (Altalhi, 2021). Dwivedi et al (2020) revealed in their recent meta-analysis based on modified UTAUT studies, that its original constructs are significantly and positively Crisis-centric distance learning model associated with the existing literature.…”
Section: Study Model and Hypothesesmentioning
confidence: 99%
“…Vinodh & Mathew demonstrate a significant association between effort expectancy and behavioral purpose through e-governance technologies (Vinodh & Mathew, 2012). Another support from other research can add to the literature to strengthen the relationship between effort expectancy and behavioral intention in pre-school teachers (Altalhi, 2021;Fadil Persada et al, 2019;Raza et al, 2021). Then, effort expectancy is significant to increase student satisfaction in doing online learning (Abugabah et al, 2015;Alajmi & Alotaibi, 2020;Cody-Allen & Kishore, 2006;Musyaffi & Muna, 2021).…”
Section: Introductionmentioning
confidence: 87%